Identification of a host collagen inducing factor from the excretory secretory proteins of Trichinella spiralis. - Mi Kyung Park; Hae-Jin Kim; Min Kyoung Cho; Shin Ae Kang; So Young Park; Se Bok Jang; Hak Sun Yu (PLoS Neglected Tropical Diseases, 2018)
BACKGROUND:In a previous study, we found that Trichinella spiralis muscle larva excretory and secretory proteins (ES-P) most likely activate collagen synthesis via TGF-β/Smad signaling, and this event could influence collagen capsule formation. METHODOLOGY/PRINCIPAL FINDINGS:In order to identify the specific collagen inducing factor, ES-P was fractionated by a Superdex 200 10/300 GL column. We obtained three large fractions, F1, F2, and F3, but only F3 had collagen gene inducing ability. After immunoscreening, 10 collagen inducing factor candidates were identified. Among them, TS 15-1 and TS 15-2 were identical to the putative trypsin of T. spiralis. The deduced TS 15-1 (M.W. = 72 kDa) had two conserved catalytic motifs, an N-terminal Tryp_SPc domain (TS 15-1n) and a C-terminal Tryp_SPc domain (TS 15-1c). To determine their collagen inducing ability, recombinant proteins (rTS 15-1n and rTS 15-1c) were produced using the pET-28a expression system. TS 15-1 is highly expressed during the muscle larval stage and has strong antigenicity. We determined that rTS 15-1c could elevate collagen I via activation of the TGF-β1 signaling pathway in vitro and in vivo. CONCLUSION/SIGNIFICANCE:In conclusion, we identified a host collagen inducing factor from T. spiralis ES-P using immunoscreening and demonstrated its molecular characteristics and functions.